Pengaruh Kinerja Dan Pengetahuan Produk Tenaga Penjual Terhadap Citra Perusahaan - Tobing, Maju L; Arvani, Sisvana Multi (Jurnal Ilmiah Manajemen Kesatuan, 2015)
This research aimed at investigating (1) whether product performance has leverage against the image of the company, (2) whether the product knowledge has an influence on the image of company, and (3) whether the performance and product bzowledge of the sales person jointly have leverage against the image of company. The number of respondents targeted is a 100 people using regression methods equation and correlation and calculated using SPSS version 20.0.Tthe research showed that performance of sales person has influence on the image of company. The regression equation of the company's image is (Y) = 2.414 + (-0.280) X1 + 0.475 (X2), where x1 is performance influence and x2 is product biowledge of sales person . The coeficient of determination obtained is 0,608 which means there is a chance of 60,8% that variable of company's image will be affected by a free variable of performance influence of sales person (x1). The remaining of 39,2% is product blowledge of a sales person influenced by other variables. Keywords : Performance and Product Knowledge